2012
DOI: 10.4194/1303-2712-v12_1_05
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The seasonal effects on the fatty acid composition of total lipid, triacylglicerol and phospholipid in the dorsal muscle of Silurus triostegus were determined by gas chromatographic (GC) method. The total polyunsaturated fatty acids (PUFA) and monounsaturated fatty acids (MUFA) were the most important groups of total lipid and statistically ranged (P<0.05) from 33.88% to 55.85% and from 23.37% to 38.71%, respectively. The major fatty acids of total lipid in all seasons were palmitic acid (16:0) in SFA, oleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
3
3
0
Order By: Relevance
“…Our findings are also in close agreement with those reported by Haliloğlu et al, (2004), Akpınar et al, (2009 and Cengiz et al, (2012) for other freshwater fish.…”
Section: Fatty Acid Profile Of Total Lipidssupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are also in close agreement with those reported by Haliloğlu et al, (2004), Akpınar et al, (2009 and Cengiz et al, (2012) for other freshwater fish.…”
Section: Fatty Acid Profile Of Total Lipidssupporting
confidence: 94%
“…C18:1 ω-9 was the most ample of the monoenes in all seasons. Our findings concerning the C18:1 ω-9 FA are almost comparable to the concentration reported by Haliloğlu et al, (2004) and Cengiz et al, (2012) for the same FA in the muscle of freshwater fish. A low level of C16:1 ω-7 lowered the MUFA contents of M. mastacembelus.…”
Section: Fatty Acid Profile Of Pl Fractionsupporting
confidence: 90%
“…The ɷ6/ɷ3 ratio of unsaturated fatty acids is associated with mortality causes from cancer and cardiovascular diseases. [ 65 ] It has been reported that this ratio is also important indicator used to compare nutritional values in fish oil [ 66,67 ] and should be kept as low as 1:1 or 2:1 in diets. [ 68,69 ] According to HMSO, [ 62 ] it was proposed that this ratio can have a maximum value of 4.…”
Section: Resultsmentioning
confidence: 99%
“…Cengiz et al. [ 67 ] suggested that a ratio between 0.2 and 1.6 constitutes a healthy human diet. The reduction of Σɷ6/ɷ3 ratio in the human diet is essential to help prevent coronary heart disease and reduce cancer risk.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, LL exposure may have caused stress in rainbow trout [ 97 ], leading to a decrease in the proportion of HUFA in muscle. On the other hand, it was found that rainbow trout [ 100 ] and Mesopotamian catfish ( Silurus triostegus ) [ 101 ] had a higher MUFA and lower PUFA in summer (long daylight) than in winter (short daylight). Xie et al (2013) [ 99 ] suggested that seasons affect fatty acids mainly related to changes in the photoperiod and temperature.…”
Section: Discussionmentioning
confidence: 99%